Do Aid for Trade flows affect Technology Licensing in Recipient Countries? - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2023)
There is an abundant literature on the economic (including trade) effects of Aid for Trade (AfT) flows. However, little attention has been devoted to the effect of AfT flows on demand for technology. The present article aims to fill this void in the literature by investigating the effect of AfT flows on technology licensing in developing countries. The analysis has used an unbalanced panel dataset of 77 countries over the period from 2002 to 2019, and mainly the two-step system generalized method of moments estimator. It has established that AfT flows foster technology licensing in countries that experience lower trade costs. In addition, the analysis has revealed that adverse environmental and external (economic and financial) shocks significantly hamper innovation, including the demand for technology licensing, and that AfT flows promote technology licensing in countries that experience lower magnitudes of such shocks. Finally, AfT flows foster technology licensing in countries that diversify their export products.
Keywords: F10; F35; L24; 330; Aid for Trade; Technology licensing; Trade costs